Pneumonia Severity Scores and Prescribing Antibiotics for Community‐Acquired Pneumonia at an Australian Hospital. (June 2013) - Brett, Jonathan; Lam, Vincent; Baysari, Melissa T; Milder, Tamara; Killen, Louise; Chau, Anthony MT; McMullan, Brendan; Harkness, John; Marriott, Deborah; Day, Richard O
ABSTRACT: Aim: To evaluate the use of pneumonia severity scores for diagnosing community‐acquired pneumonia (CAP) and to assess whether antibiotic prescribing was compliant with guidelines as determined by the calculated pneumonia severity score. Method: A retrospective chart review was undertaken of consecutive adults admitted via the emergency department with a diagnosis of CAP during a 6‐month period. Charts were reviewed for symptoms and radiographic evidence of pneumonia and for recorded pneumonia severity scores. Pneumonia severity scores were calculated using CORB, CURB‐65 and SMART‐COP for patients with available data and used to assess compliance with the Therapeutic Guidelines: Antibiotic . Results: Of the 204 patients reviewed Of the 204 patients reviewed CURB‐65 and SMART‐COP scores for the remaining 68 patients, 13 (19%), 3 (4.4%) and 1 (3.6%) patients had severe pneumonia. 93% of patients received ceftriaxone. An average of 8% of patients were prescribed antibiotics compliant with the Therapeutic Guidelines: Antibiotic . Compliance varied with the pneumonia severity scoring tool used. Conclusion: Pneumonia severity scores were rarely calculated to guide treatment and antibiotic prescribing for CAP. Compliance with the Therapeutic Guidelines: Antibiotic was poor and varied with the pneumonia severity scoring tool used. An easy‐to‐use pneumonia severity score to guide patient admission and choice of antibiotic is needed.